Rhodium(III) and iridium(III) complexes with quinolyl-functionalized cp ligands: synthesis and catalytic hydrogenation activity - Kohl, Gerald; Pritzkow, Hans; Enders, Markus (European journal of inorganic chemistry, 2008)
Bis(ethene) complexes of rhodium(I) and iridium(I) with 8-quinolylcyclopentadienyl ligands (CpQ and CpQ*) were oxidized by a photochemically induced reaction with chlorine-containing solvents or by treatment with iodine. Upon this oxidation, the quinoline ring rotates and the N donor coordinates to the metal centers. Substitution of the halogenido ligands through acetato groups leads to highly soluble derivatives, in which the acetate moiety acts as a monodentate or bidentate ligand. The new Rh complexes were evaluated as catalysts for the hydrogenation of 1-hexene. The coordinatively saturated complexes show hydrogenation activity without the necessity of external bases. The catalytic activity is highest for the cationic complex [CpQ*Rh(O2CCH3)]+PF6- (6b), which contains a bidentate acetato ligand. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Published online: August 19, 2008
Gesehen am 23.11.2022